2019
DOI: 10.1002/mrm.28049
|View full text |Cite
|
Sign up to set email alerts
|

RF heating of deep brain stimulation implants in open‐bore vertical MRI systems: A simulation study with realistic device configurations

Abstract: Purpose Patients with deep brain stimulation (DBS) implants benefit highly from MRI, however, access to MRI is restricted for these patients because of safety hazards associated with RF heating of the implant. To date, all MRI studies on RF heating of medical implants have been performed in horizontal closed‐bore systems. Vertical MRI scanners have a fundamentally different distribution of electric and magnetic fields and are now available at 1.2T, capable of high‐resolution structural and functional MRI. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

7
0

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…This oversimplified approach to MRI safety assessment is concerning for two reasons. First, as RF heating is highly sensitive to implant's configuration and its orientation with respect to MRI electric field (14)(15)(16)(17)(18)(19)(20)(21)(22), and as trajectory of DBS leads is substantially variant among patients (23), basing safety inferences on few tested configurations can expose a large number of patients to undue risk. Second, conclusions drawn from studies in single-material box-shaped phantoms may not apply to the realistic cases, as the distribution of electromagnetic fields depend upon the geometry and composition of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…This oversimplified approach to MRI safety assessment is concerning for two reasons. First, as RF heating is highly sensitive to implant's configuration and its orientation with respect to MRI electric field (14)(15)(16)(17)(18)(19)(20)(21)(22), and as trajectory of DBS leads is substantially variant among patients (23), basing safety inferences on few tested configurations can expose a large number of patients to undue risk. Second, conclusions drawn from studies in single-material box-shaped phantoms may not apply to the realistic cases, as the distribution of electromagnetic fields depend upon the geometry and composition of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Such off‐label studies have relied on in‐home safety assessments mostly performed in ASTM‐like phantoms (ie, the box‐shaped phantom filled with a single material), and with a limited number of DBS device configurations 14,15 . This oversimplified approach to MRI safety assessment is concerning for two reasons: First, RF heating is highly sensitive to the configuration of an implant and its orientation with respect to MRI electric field 10,16–20 . As trajectories of DBS leads are substantially variant among patients, basing safety inferences on a few tested configurations can expose a large number of patients to undue risk 21 .…”
mentioning
confidence: 99%
“…As the orientation and phase of MRI incident electric field along the trajectory of an elongated implant has a substantial effect on the local SAR at the electrode tips [1,[3][4][5][6][7][8], we hypothesized that vertical scanners generate a statistically different RF heating compared to horizontal systems. Our hypothesis is based on a preliminary study of RF heating of DBS implants in three (3) realistic patient models which showed 4-to 14-fold reduction in the maximum local SAR around DBS electrodes in a vertical 1.2 T coil compared to a horizontal 1.5 T coil [2]. Here we extend our previous work to include a cohort of 20 patient models with bilateral DBS leads (40 lead models in total) with realistic trajectories.…”
Section: Introductionmentioning
confidence: 84%
“…Vertical scanners, originally introduced as low-field open-bore systems, are now available at high field strength capable of high-resolution structural and functional studies. No literature (except our recent work [2]) exists on RF heating of DBS implants inside this class of scanners which have a 90 rotated transmit coil and thus generate a fundamentally different distribution of electric and magnetic fields inside patient's body. As the orientation and phase of MRI incident electric field along the trajectory of an elongated implant has a substantial effect on the local SAR at the electrode tips [1,[3][4][5][6][7][8], we hypothesized that vertical scanners generate a statistically different RF heating compared to horizontal systems.…”
Section: Introductionmentioning
confidence: 99%